Intrapleural Epinephrine Irrigation for Massive Malignant Hemothorax - Huang, Pei-Ming; Chou, Nai-Kuan; Lin, Tzu-Hsin; Chen, Chiung-Nien (The Thoracic and Cardiovascular Surgeon, 2016)
Massive malignant hemothorax (MMH) is a rare and serious complication encountered in the field of oncology and can be life threatening. It is often difficult and complex to manage. Herein, we present cases of four patients who had MMH and in whom a hemothorax was successfully stopped via continuous intrapleural irrigation with epinephrine (5-mg epinephrine/1,000-mL normal saline, infused at 100 mL/h) instead of a conventional surgical approach. Although no patient deaths were attributed to intractable bleeding, two deaths were related to multiple organ failure. Despite the limited number of cases, this method was a convenient, effective, and inexpensive alternative to open surgical or thoracoscopic drainage for MMH.
Keywords: intrapleural treatment; hemothorax; malignancy